Improved Conditions for the Visible-Light Driven Hydrocarboxylation by Rh(I) and Photoredox Dual Catalysts Based on the Mechanistic Analyses - Murata, Kei; Numasawa, Nobutsugu; Shimomaki, Katsuya; Takaya, Jun; Iwasawa, Nobuharu (Frontiers in Chemistry, 2019)
The improved catalytic conditions and detailed reaction mechanism of the visible-light driven hydrocarboxylation of alkenes with CO2 by the Rh(I) and photoredox dual catalysts were investigated. The use of the benzimidazoline derivative, BI(OH)H, as a sacrificial electron donor was found to increase the yield of the hydrocarboxylated product by accelerating the reduction process. In addition, the incorporation of the cyclometalated Ir(III) complex as a second photosensitizer with [Ru(bpy)3]2+ photosensitizer also resulted in the promotion of the reduction process, supporting that the catalytic cycle includes two photochemical elementary processes: photoinduced electron and energy transfers.